2021
DOI: 10.1097/mcg.0000000000001550
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Biological Therapy in Chronic Antibiotic Refractory Pouchitis

Abstract: Background: Pouchitis is the most common long-term complication after ileal pouch-anal anastomosis in patients with ulcerative colitis. Those with ≥3 episodes of pouchitis/year and symptoms despite antibiotics are considered to have chronic antibiotic refractory pouchitis (CARP). While several agents including probiotics, steroids and immunomodulators have been used, treatment of CARP remains challenging. We conducted a systematic review and meta-analysis evaluating the safety and efficacy of vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Biological therapy is a good therapeutic option in patients with chronic refractory pouchitis and CD of the pouch. 25 29 , 33 , 36 , 38 One meta-analysis reported that clinical remission after induction of anti-TNF agents was more common in CD than in chronic pouchitis (64% versus 10%). 27 Nonetheless, our data show that they would be a useful alternative long-term option, especially for patients with previous exposure to steroids who develop dependence (85% versus 15%, p = 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Biological therapy is a good therapeutic option in patients with chronic refractory pouchitis and CD of the pouch. 25 29 , 33 , 36 , 38 One meta-analysis reported that clinical remission after induction of anti-TNF agents was more common in CD than in chronic pouchitis (64% versus 10%). 27 Nonetheless, our data show that they would be a useful alternative long-term option, especially for patients with previous exposure to steroids who develop dependence (85% versus 15%, p = 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…First, the interpretation of some results could be challenging because of the different mechanisms of action of included drugs. However, this kind of approach has been done for other therapeutic areas (e.g., biologics in ulcerative colitis [ 49 ]) and could be interesting to provide additional data to guide the NAFLD drug pipeline properly. Second, studies reporting cirrhotic-related outcomes were scarce, precluding making robust analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Other targeted agents, notably infliximab, adalimumab and ustekinumab, have also been shown to be effective, and benefits of tofacitinib have been reported. Their use can be considered on a case-by-case basis, taking into account the benefits and risks of therapy [ 114 , 119 , 123 , 131 136 ].…”
Section: Othermentioning
confidence: 99%